Exports and long-run growth: The case of Spain, 1850-2017 - Oscar Bajo-Rubio (Global Labor Organization (GLO), 2020)
We analyse in this paper the relationship between international trade and economic growth from the point of view of one of the most traditional hypotheses within this field, namely, the export-led growth hypothesis, for the case of Spain in a long-term perspective of almost 170 years. Exports seem to have played a positive, though modest, role in promoting economic growth in the Spanish economy over the whole period, mostly due to the higher productivity associated with the export sector. The contribution of exports to growth, however, seems to have been stronger in the final years of the 19th century, unlike the rest of the period, where it proved to be very small.
Keywords: F41; F43; N10; O47; 330; Exports; Economic growth; Spanish economy